POWER MANAGEMENT CONTROL OF A HYBRID PV-GENSET SYSTEM USING ZELIO LOGIC SMART RELAY - Soeprapto Soeprapto; Unggul Wibawa; Mahfudz Shidiq (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2016)
Power management control using Zelio Logic Smart Relay is applied as a means to make automatic power transition from battery to generator and vice versa. The design of a hybrid system in a laboratory scale is described including the design of software part using Zelio Soft2 (ANONIM 3, 2014). The experiment results show that the values of voltage and power output of the solar cell will increase with the increasing intensity of the sun, while the current will be decreasing. The current sensor used in the system is able to detect the linear changes of current flowing into the load and to respond in a form of voltage to be inputted into Zelio. The automatic operation of genset can be performed properly and the SFC optimum value of the genset of 2.8 kW, 220 V, 50 Hz is 0.67 l/kWh under 72% loading of the generator capacity. Automatic switching of the hybrid system can be realized based on the sensing results of battery voltage and load voltage with the help of Zelio. Load is supplied through the battery inverter when the battery voltage exceeds its voltage, it is supplied directly from the genset and the relay is activated to charge the battery.